Use of biomarkers as prognostic indicators in dogs with natural heartworm (2018)
Heartworm disease is a parasitic illness caused by the Dirofilaria immitis nematode. In its developed form, remains in the pulmonary artery and right side of the heart, resulting in pulmonary thromboembolism, myocarditis, and inflammation. A retrospective study was made in which was evaluated the usefulness of the Dimer-D, troponin I and C-reactive protein in sick dogs naturally infected with heartworm. There were evaluated the concentrations of D-Dimer, troponin I and C-reactive protein in 23 dogs, analyzed hematological variables, the presence or absence of microfilariae, the pulmonary hypertension and clinical signs. The respiratory problems were the most frequent clinical signs including dyspnea (74%), cough (30%), pulmonary hypertension (57%), and other signs of inflammation or pulmonary thromboembolism. Hematological changes were not found. Elevations of the Dimer-D were found in 73.9% of cases, where the patients with microfilariae (69.6%) showed higher values compared to amicrofilaremics (30.4%); males had a higher average (3,857.83 ng ml-1) compared to females (1,714.0 ng ml-1). Troponin I and C-reactive protein had elevations in 21.7 - 39.1% of cases without significant changes compared to sex or microfilariae. The measurement of Dimer-D, troponin I and C-reactive protein complements for the diagnosis, prognosis and therapeutic control in patients with D. immitis indicated inflammation, pulmonary thromboembolism and/or myocarditis.